Monitoring the impact of COVID-19 in Myanmar: Rice millers – October 2020 survey round - Goeb, Joseph; Synt, Nang Lun Kham; Zone, Phoo Pye; Tang, Yulu (International Food Policy Research Institute, 2020)
To understand how Myanmar’s rice value chain has been affected by the COVID-19 crisis, a series of phone interviews is being conducted with rice millers from Ayeyarwady, Bago, and Yangon. This report presents results from the fourth interview round conducted in October 2020. These results capture the effects of the second wave of COVID-19 related lockdowns that began in September.